Pengaruh Leverage, Ukuran Perusahaan, Pertumbuhan Perusahaan, Profitabilitas, dan Efisien Biaya (Studi Empiris Pada Bank Umum Syariah Di Indonesia Tahun 2018-2022) - Ramadhani, Astrid Maya; Kurniawati, Lintang (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to investigate the impact of leverage, companynsize, company growth, profitability, and cost efficiency on the disclosure of Islamic Social Reporting (ISR) in thenannual report of Islamic Commercial Banks in Indonesianfor the period 2018-2022. The research variable data obtained consists of secondary data pertaining to leverage, firm size, corporate growth, profitability, costnefficiency, and the Islamic Social Reportinn(ISR) index. The purposive samplingxtechnique was used to choose the sample. Data analysis is conducted using classical assumption tests and descriptive statistical, including normality, heteroscedasticity testing, multicollinearity testing and autocorrelation testing. The model feasibility test comprises the coefficient determinationtest, f test, and tntest. The findings from the multiple regression analysis indicate that the size of a corporation has a notable impact on the extent to which Islamic CommercialBanks in Indonesia disclose ISR during the period of 2018-2022. The determinants of leverage, corporate growth, profitability, and cost efficiency do not exert a substantial impact on the disclosure ofIISR at Islamic Commercial Banks(BUS) innIndonesia throughout the period from 2018 to 2022.